طبيعة الصورة والكلمة في صناعة أدب الأطفال بالجزائر - قزويط, أحمد; سعيد بن يحي, بهون علي (University of Eloued جامعة الوادي, 2024)
نحاول في هذه الورقة البحثية أن نتطرق إلى طبيعة الصورة وتأثيراتها وظلالها على الأدب والقصة الطفلية على وجه الخصوص، وسواء أكانت الصورة حقيقية أم مجازية في الخطابات النصية، وسواء أكانت قراءات الأقدمين والحداثيين ملبية للغرض في تناول الصورة بما يسد عوز أطفالنا في عالمهم المحسوس لحياة أفضل، أو في عالمهم المتخيل.. In this research paper, we try to address the nature of the image and its effects and shadows on literature and the children’s story in particular, and whether the image is real or figurative in textual discourses, and whether the readings of the ancients and moderns fulfill the purpose of dealing with the image in a way that fills the need of our children in their tangible world for a better life, Or in their imagined world
مقال. مجلة علوم اللغة العربية وآدابها. مج16 . ع.01. جامعة الوادي